Pengaruh Permainan Pancing Huruf Terhadap Kemampuan Mengenal Huruf Abjad Anak Usia Dini - Fatihatul Fuadah, Kholilah; Kurnia, Aam; Muftie, Zaenal (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to determine the effect of using the fishing letters game on the ability to recognize alphabet letters among early childhood students in Group A at RA Al-Muhajir. The type of research used is quantitative research. The subjects of the study were 24 children, while the object was the ability to recognize alphabet letters. Data collection techniques included observation and documentation, and data analysis was conducted using statistical tests to determine the effect. The results showed a significant influence between the use of the fishing letters game compared to the bussy book media in improving early childhood letter recognition skills. The conclusion of this study is that the fishing letters game is effective in significantly enhancing the ability to recognize alphabet letters in early childhood and can be used as an alternative, engaging, and enjoyable learning medium